(untitled) (Eurasian Journal of Philology Science and Education, 2019)
Philosophical and aesthetic model of the world by A.K. Tolstoy includes the belief in both existence of the real world related common sense and irrational world rejected common logic approach. According writer’s view, the irrational world is out of reasonable human understanding and nevertheless is capable to interfere in the real world. The influence of the irrational world on people life may be positive and very harmful at the same time.This research trend of art creativity A.K. Tolstoy supports properly interpretation of the main author fiction idea and represents philosophical and esthetic outlook of the writer.